Formation of Independent Children's Character Through Dialogue of Faith in Allah - Nurul Riyatin (International Journal of Interdisciplinary Research, 2025)
Independence is an important aspect of a child's character development, allowing them to take initiative, take responsibility for their actions, and overcome challenges effectively. Dialogue of faith in Allah Swt , as a process of reflection and internalization of spiritual values, is believed to contribute to fostering independence in children. This article aims to review the scientific literature in the last five years regarding the influence of faith dialogue in Allah Swt on the formation of children's independent character. The method used is a systematic literature review by identifying, selecting, and analyzing relevant articles from various databases. The results of the study show that dialogue of faith in Allah Swt can encourage children to develop confidence, decision-making skills, self-discipline, and perseverance, which are important components of independence. Dialogue of faith in Allah Swt also provides a strong moral foundation for children to act independently while still considering ethical values and social norms. This article provides important implications for children's character education in the family, school, and community environment, by emphasizing the importance of faith dialogue as a means to foster independence based on spiritual values.